The effect of exercise-induced muscle damage on perceived exertion and cycling endurance performance - Twist, C.; Eston, R. G. (European Journal of Applied Physiology, 2009)
This study evaluated the effects of exercise-induced muscle damage (EIMD) on fixed-load cycling and 5-min time-trial performance. Seven recreational athletes performed two submaximal fixed-load exercise bouts followed by a 5-min time-trial before, 48 and 168 h following 100 counter-movement jumps. Measurements of VO2, heart rate, RER and blood lactate concentration remained unchanged during the fixed-load bouts following jumping exercise. However, VEand VE/VO2increased (P < 0.05) at 48 h. RPE values were higher at 48 h as were the ratio of RPE:HR and RPE: VO2(P < 0.05). In the time-trial, mean VO2peak power output, mean power output, distance covered and post exercise blood lactate were lower at 48 h (P < 0.05). RPE remained unchanged between trials. These findings indicate that the ventilatory equivalent for oxygen and perceived exertion at submaximal work rates are increased 48 h following eccentric exercise. Furthermore, EIMD increases perceived exertion and impairs performance during a 5-min all-out effort.